APLASTIC ANEMIA - Dharma Laksmi, Ni Made; Herawati, Sianny; Sutirta Yasa, Wayan Putu (E-Jurnal Medika Udayana; vol 2 no 7 (2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Aplastic Anemia describes a disorder of the clinical syndrome is marked by a deficiency of red blood cells , neutrophils , monocytes and platelets in the absence of other forms of bone marrow damage . Aplastic anemia is classified as a rare disease in developed countries the incidence of 3-6 cases / 1 million inhabitants / year . The exact cause of someone suffering from aplastic anemia also can not be established with certainty , but there are several sources of potential risk factors. Prognosis or course of the disease varies widely aplastic anemia , but without treatment generally gives a poor prognosis /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Aplastic Anemia